UV photoreduction-driven heterogeneous fenton-like process: Long-term reactivation of fenton sludge-derived biochar and enhanced acetaminophen degradation - Yang, Heejin; Jung, Sung Hyo; Lee, Jong Ho; Cho, In Sun; Park, Seong Jik; Lee, Chang Gu (Journal of Water Process Engineering, 2024)
The Fenton process has been employed in a wide range of applications, including the treatment of wastewater, due to its distinctive characteristics, but disposing of the iron sludge waste that it generates remains a challenge. As a sustainable and effective solution to this problem, the preparation of Fenton sludge (FS) biochar (FSB) and its subsequent use in water treatment has been proposed. In the present study, FSB was employed as a catalyst for the UVC-induced activation of potassium peroxydisulfate (PDS) in the removal of the target contaminant acetaminophen (ACP). The FSB was prepared by pyrolyzing FS (900 °C, 120 min, N2 atmosphere), and X-ray diffraction analysis confirmed the presence of iron such as zero-valent iron (Fe0) and iron carbide (Fe3C) on its surface. The FSB/PDS/UVC system achieved an ACP removal efficiency of 100.0 ± 0.0 % in a batch experiment (ACP = 20 mg/L, FSB = 0.2 g/L, PDS = 1 mM, time = 60 min), while the ACP removal rate constant was higher in the FSB/PDS/UVC photo-Fenton-like system (0.309 /min) than in the FSB/PDS Fenton-like system (0.281 /min). The reusability of the FSB in the FSB/PDS/UVC system was tested over 15 cycles and the results showed that, unlike the FSB/PDS system, the catalytic performance of the ACP degradation rate remained consistent (99 %). Overall, UVC irradiation promoted photoreduction, accelerating the in-situ Fe(II)/Fe(III) redox cycle and improving the regeneration of the FSB. This work provides insights into sustainable FS treatment strategies and highlights the potential for the use of FSB in wastewater treatment.
Keywords: Anthropogenic pharmaceutical; Fenton sludge biochar; Long-term reuse; Photoreduction; Solid waste utilization